Comparative Macroeconomic Dynamics in the Arab World : A Panel Var Approach - Kireyev, Alexei (IMF Working Papers; Working Paper ;, 2000)
The paper presents a comparative analysis of macroeconomic dynamics of 18 Arab countries based on a panel vector autogression estimation. Comparing growth performance, fiscal and current account developments in these countries, the study concludes that (1) in the short run, external and country-specific factors play an almost equal role in explaining macroeconomic fluctuations, but in the long run external factors dominate; (2) on average, program countries are less vulnerable to adverse exogeneous shocks than nonprogram countries; (3) to mitigate the negative impact of an external shock, domestic policy response should be consistent with the size of the shock.